2009
DOI: 10.1007/s00380-008-1137-7
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits nuclear factor κB activation and decreases serum high-sensitivity C-reactive protein level in experimental atherogenesis of rabbits

Abstract: Previous studies demonstrated that metformin has obvious antiatherogenic properties, but the exact mechanism remains unclear. Therefore, we established an atherosclerotic rabbit model in order to investigate the potential effects of metformin on transcription factor nuclear factor kappaB (NF-kappaB) and serum high-sensitivity C-reactive protein (hs-CRP) level, which had been regarded as proatherogenic factors. New Zealand rabbits were randomly divided into three groups: a control group (n = 8), an atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
57
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 48 publications
4
57
0
4
Order By: Relevance
“…[22][23][24] Consistent with previous studies, [25][26][27][28][29] our study also indicates that metformin prevents activation of NF-jB. In the present study, we have shown that the expression of LPS-induced NF-jB in ciliary bodies as well as retinal tissues was suppressed in metfomin-treated rats.…”
Section: Discussionsupporting
confidence: 81%
“…[22][23][24] Consistent with previous studies, [25][26][27][28][29] our study also indicates that metformin prevents activation of NF-jB. In the present study, we have shown that the expression of LPS-induced NF-jB in ciliary bodies as well as retinal tissues was suppressed in metfomin-treated rats.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with some findings from experimental models in which metformin reduced levels of several inflammatory mediators (IL-6, IL-1β, TNF-α, prostaglandin E2, nitric oxide) in a dose-dependent manner (Hyun et al, 2013). Also for metformin, one of the biological mechanisms underpinning this anti-inflammatory effect was the inhibition of transcription factor NF-κB (Hyun et al, 2013; Li et al, 2009). Taken together these findings indicate metformin as a potential alternative strategy to caloric restriction in reducing inflammaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, metformin inhibition of complex 1 function in isolated mitochondria requires very high metformin concentrations (18). In the context of atherosclerosis, metformin inhibits NF-κB activation and decreases C-reactive protein levels (20), and it inhibits the inflammatory response via a pathway involving AMPK and the tumor suppressor PTEN (21). Not much is known about how metformin mediates any of its anticancer effects.…”
mentioning
confidence: 99%